2002
DOI: 10.1148/radiol.2241011062
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Detection: Evaluation of a Mass-Detection Algorithm for Computer-aided Diagnosis—Experience in 263 Patients

Abstract: This mass-detection algorithm had a high sensitivity for detection of malignant masses. It may be useful as a second opinion in mammographic interpretation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 16 publications
0
44
0
3
Order By: Relevance
“…Various researchers have developed CAD methods for breast imaging modalities-including mammography, US, and MR imaging-and for combined modalities for the tasks of automated lesion segmentation, feature extraction, and lesion characterization (11)(12)(13)(30)(31)(32)(33)(34)(35). In addition, several observer studies of all three of these modalities have revealed the potential usefulness of CAD in clinical settings (36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…Various researchers have developed CAD methods for breast imaging modalities-including mammography, US, and MR imaging-and for combined modalities for the tasks of automated lesion segmentation, feature extraction, and lesion characterization (11)(12)(13)(30)(31)(32)(33)(34)(35). In addition, several observer studies of all three of these modalities have revealed the potential usefulness of CAD in clinical settings (36)(37)(38)(39)(40).…”
Section: Discussionmentioning
confidence: 99%
“…The 25% threshold was selected as described in our previous study. 30 To evaluate the performance of our bilateral LDA classifier, the test discriminant scores were analyzed using receiver operating characteristic (ROC) methodology. 31 The accuracy for classification of mass and normal tissue was evaluated as the area under the ROC curve, A z .…”
Section: Evaluation Methods-mentioning
confidence: 99%
“…Feature extraction and FP reduction-FP classification in our mass detection system is accomplished by a three-stage classification scheme. 36,44 For each suspicious object, eleven morphological features are extracted. Rule-based classification and a linear discriminant analysis (LDA) classifier using all 11 morphological features as input predictor variables are trained to remove the detected structures that are substantially different from breast masses.…”
Section: B Methodsmentioning
confidence: 99%
“…34 We have developed a CAD system for the detection of masses on SFMs in our previous studies. 30,35,36 We are developing a mass detection system for mammograms acquired directly by a FFDM system. In this study, we adapted our mass detection system developed for SFMs to FFDMs by optimizing each stage and retraining.…”
mentioning
confidence: 99%